Pengaruh Corporate Social Responsibility, Leverage & Ukuran Perusahaan Terhadap Profitabilitas Bank Umum Syariah Periode 2018-2023 - Phara Kautsarna Beela; Abdul Ghoni; Nur Haida (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
The research aims to analyze the influence of Corporate Social Responsibility (CSR), leverage, and company size on the profitability of Islamic Commercial Banks in Indonesia during the 2018–2023 period. Profitability is measured using the Return on Assets (ROA) ratio. The research applies a quantitative approach with panel data regression analysis. The sample consists of six Islamic Commercial Banks selected through purposive sampling based on criteria such as consistent publication of annual and sustainability reports, ongoing CSR implementation, and continuous profitability during the observation period. The results show that CSR has no significant effect on profitability, leverage also has no significant effect, while company size has a significant positive effect on profitability. The research is expected to contribute to the academic literature in Islamic banking and provide practical insights for bank management in formulating strategies related to CSR implementation, debt management, and business expansion